2014
DOI: 10.1007/s10856-014-5292-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physiochemical characterization, and biocompatibility of a chitosan/dextran-based hydrogel for postsurgical adhesion prevention

Abstract: An amine-functionalized succinyl chitosan and an oxidized dextran were synthesized and mixed in aqueous solution to form an in situ chitosan/dextran injectable, surgical hydrogel for adhesion prevention. Rheological characterization showed that the rate of gelation and moduli were tunable based on amine and aldehyde levels, as well as polymer concentrations. The CD hydrogels have been shown to be effective post-operative aids in prevention of adhesions in ear, nose, and throat surgeries and abdominal surgeries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 42 publications
6
44
0
3
Order By: Relevance
“…Current phase I/II trials of a chitosan-dextran hydrogel demonstrate improved clinical outcomes after sinus surgery (11). When prepared in situ, succinyl-chitosan and dextran-aldehyde form a nontoxic, biocompatible, biodegradable gel that facilitates postoperative wound healing by promoting homeostasis and preventing adhesions (11)(12)(13)(14)(15). The latter is a particularly important postsurgical complication of endoscopic sinus surgery that frequently causes surgical failure (16).…”
mentioning
confidence: 99%
“…Current phase I/II trials of a chitosan-dextran hydrogel demonstrate improved clinical outcomes after sinus surgery (11). When prepared in situ, succinyl-chitosan and dextran-aldehyde form a nontoxic, biocompatible, biodegradable gel that facilitates postoperative wound healing by promoting homeostasis and preventing adhesions (11)(12)(13)(14)(15). The latter is a particularly important postsurgical complication of endoscopic sinus surgery that frequently causes surgical failure (16).…”
mentioning
confidence: 99%
“…Chitosan and dextran, which are both naturally derived polysaccharides, are in vivo biodegradable and biocompatible [Khor, 2002;Shkurupiy et al, 2008;Cabral et al, 2014]. The results obtained in this study showed no difference in the ABR thresholds before and 4 weeks after intratympanic injection of CDH, which indicates that CDH has no ototoxic effect on GPs.…”
Section: Discussionmentioning
confidence: 51%
“…CD-25 hydrogel gelation time and the aldehyde level in DA-25 were as previously described. 20,25 SC was sterilized by autoclaving prior to s.c. injection, and DA-25 was sterilized by filtration with 0.22 mm pore-size cellulose acetate filters (Millipore, North Ryde, New South Wales). Unlabeled CD-25 hydrogel was used for the inflammatory response study.…”
Section: Animalsmentioning
confidence: 99%
“…19 Our group has previously published an optimized route for the synthesis of the chitosan/dextran (CD) hydrogel components, succinyl chitosan (SC), and oxidized dextran (DA). 20 The amine-functionalized SC and DA are mixed in aqueous solutions to form an in situ injectable hydrogel. This CD hydrogel was developed as a post-operative aid in endoscopic sinus surgeries (ESS) in vivo in both animal and human trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation